Zwischen Pauschalisierung und Differenzierung: Einstellungen gegenüber Muslim*innen und dem Islam in Deutschland - Diekmann, Isabell; Janzen, Olga

Ökologische Verantwortung für zukünftige Generationen - Diekmann, Isabell (Vielfalt leben - Gesellschaft gestalten)

Do Guided Mosque Tours Alleviate the Prejudice of Non-Muslims against Islam and Muslims? Evidence from a Quasi-Experimental Panel Study from Germany - Janzen, Olga; Diekmann, Isabell; Tsolak, Dorian; Salentin, Kurt (Zeitschrift für Religion, Gesellschaft und Politik)
Background Anti-Muslim and anti-Islam attitudes are widespread in contemporary western societies. A grassroots movement of mosques tries to reduce prejudice by organizing guided mosque tours for non-Muslims. While this is an opportunity for intergroup contact in a social psychological sense, contact occurs under sometimes difficult conditions. As yet, its effects have not been investigated empirically. Objective We examine (a) whether visits have an immediate and medium-term effect on prejudice toward Islam and (b) how they change the visitors’ subjective images of Muslims. Methods (a) We survey N = 324 secondary school students in a three-wave panel study in 6 guided mosque tours in different parts of Germany, including a control sample. The tour programme was in line with common practice in the mosques. Standardized measurements were taken immediately before and after the tour and again several months later. (b) We asked about subjective images of Muslims and had subjects report their spontaneous associations with the term Muslim. Results (a) Most, but not all, mosque visits significantly alleviate anti-Islam prejudice in the short term. The effects fall off after several months. (b) After the visit, the image of Muslims possessed more concrete religious content, while negative and menacing associations, such as oppression of women, threat, or so-called Islamic State have decreased. Conclusions Outgroup contact in a mosque works as predicted by the intergroup contact research, even under less than optimal conditions. However, there is potential for improvement of the setup of tours in the interest of a more sustainable impact.
Keywords: Intergroup contact; Anti-Islam attitudes; Anti-Muslim attitudes; Prejudice; Youth

Loneliness among International Chinese Students in Germany: Exploring the Role of Personal Networks and Experienced Discrimination - Diekmann, Isabell; Bilecen, Başak; Faist, Thomas
The experience of loneliness is common among international students who study in a foreign country, away from their home. Loneliness refers to the difference between the actual and desired social relationships. In the context of international student mobility, feelings of loneliness may be influenced not only by having a ‘sufficient’ number of social ties, but also other study-abroad-related stressors such as discrimination and not being able to make new cross-national friendships. In this article, we explore the predictors of loneliness among Chinese international students in Germany by examining both their social networks and the difficulties they face while studying abroad. Through our analysis of a unique dataset, we discover that when international students have an equal number of emotionally supportive ties, those with larger networks tend to experience less loneliness compared to those with smaller networks. Furthermore, having a romantic partner is associated with lower levels of loneliness. Additionally, we find that international Chinese students who encounter discrimination and struggle to form cross-national friendships report higher levels of loneliness. By delving into these findings, our research contributes valuable insights to the Special Issue, offering a novel examination of personal networks among international students in Germany. Keywords: international student mobility, loneliness, personal networks, emotional support, friendship, discrimination, China, Germany

Digitalisierung und Umwelt – eine verflochtene Digitalgeschichte der Gegenwart im Angesicht des Klimawandels - Schmitt, Martin
Keywords: Digitalisierung; Digitalgeschichte; Umweltgeschichte; Anthropozän; Computer; Rechenzentrum; Digital History

Conference report “Why Muslims? Current Scientific Observations and Challenges on Anti- Muslim Attitudes and Racism” - Diekmann, Isabell (#IKGScienceBlog)

Die Vorgeschichte der „sozialen Medien“. Über die Träume digitaler Vergemeinschaftung und freier Kommunikation - Schmitt, Martin (Soziale Medien – wie sie wurden, was sie sind)
Sind „soziale Medien“ überhaupt ein Thema für die Geschichtswissenschaft? Ja, denn die längere Geschichte der Digitalisierung, in der die „sozialen Medien“ einzuordnen sind, zählt bereits über 80 Jahre. Konrad Zuse und andere Ingenieure entwickelten seit 1941 die ersten Digitalcomputer, Unternehmer*innen, Wissenschaftler*innen und Staatenlenker*innen setzten diese seit den 1950er Jahren für ihre Zwecke ein, die Zivilgesellschaft adaptierte sie in den darauffolgenden Dekaden – all das prägte die sozio-digitale Landschaft der späteren „sozialen Medien“. Als unmittelbar „nach dem Boom“ etwa um 1970 zahlreiche Industriegesellschaften einen strukturellen Wandel in Wirtschaft, Gesellschaft und Politik durchlebten, war eine Antwort darauf die vermehrte Digitalisierung und Vernetzung. Daraus entwickelte sich die 1990er Jahre als markante Dekade von World Wide Web, Google und Chatdiensten. Die Entwicklung der „sozialen Medien“ ist also unter anderem in eine ökonomische und gesellschaftliche Entwicklung der Aufmerksamkeitsökonomie und in die längeren Veränderungen von Wirtschafts- und Gesellschaftsordnungen der Ausdifferenzierung und partiellen Individualisierung seit den 1960er Jahren einzuordnen. Dadurch lässt sich besser verstehen, welche Prämissen ihnen zugrunde lagen, welche Möglichkeitsräume und Probleme sich daraus ergaben und warum sie die heutige Öffentlichkeit in einer bestimmten Art und Weise dominieren – ohne sie jedoch zu determinieren.
Keywords: Digitalgeschichte; Soziale Medien; Technikgeschichte; World Wide Web; Digitalisierung

Vocational Teacher Education in a “COVID-19 Semester” - Jonas-Ahrend, Gabriela (A Pedagogical View of the COVID-19 Pandemic)

Geschichtskulturen im digitalen Wandel? – Zu den Gründen und Zielen dieses Bandes - Hartung, Olaf (Geschichtskulturen im digitalen Wandel?)

Historisches Lernen in einer ‚(Geschichts-)Kultur der Digitalität‘? - Hartung, Olaf (Geschichtskulturen im digitalen Wandel?)

Barkhausen Noise‐ and Eddy Current‐Based Measurements for Online Detection of Deformation‐Induced Martensite During Flow Forming of Metastable Austenitic Steel AISI 304L - Rozo Vasquez, Julian; Kanagarajah, Hanigah; Arian, Bahman; Kersting, Lukas; Homberg, Werner; Trächtler, Ansgar; Walther, Frank (Engineering Reports)
ABSTRACT This paper deals with micromagnetic measurements for online detection of strain‐induced α′‐martensite during plastic deformation of metastable austenitic steel AISI 304L. The operating principles of the sensors are magnetic Barkhausen noise (MBN) and eddy currents (EC), which are suitable for detection of microstructure evolution due to formation of ferromagnetic phases. The focus of this study was put on the qualification of different micromagnetic techniques and different measurement systems under conditions similar to the real ones during production, which is crucial for implementation of a property‐controlled flow forming process. The investigation was carried out on tubular specimens produced by flow forming, which have different content of α′‐martensite. To characterize the sensitivity of the sensors, different contact conditions between sensors and workpieces were reproduced. MBN sensors are suitable for detecting amount of α′‐martensite, but the measurements are affected by the surface roughness. This entails that the calibration models for MBN sensors must take account of these effects. EC sensors show a closer match with the amount of α′‐martensite without having major affectation by other effects.

‘Cultural Studies – The Role and Relevance of History’: 17. Weiterbildungsseminar der Deutschen Gesellschaft für das Studium Britischer Kulturen - Behler, Felix

Barkhausen Noise‐ and Eddy Current‐Based Measurements for Online Detection of Deformation‐Induced Martensite During Flow Forming of Metastable Austenitic Steel AISI 304L - Rozo Vasquez, Julian; Kanagarajah, Hanigah; Arian, Bahman; Kersting, Lukas; Homberg, Werner; Trächtler, Ansgar; Walther, Frank (Engineering Reports)
ABSTRACT This paper deals with micromagnetic measurements for online detection of strain‐induced α′‐martensite during plastic deformation of metastable austenitic steel AISI 304L. The operating principles of the sensors are magnetic Barkhausen noise (MBN) and eddy currents (EC), which are suitable for detection of microstructure evolution due to formation of ferromagnetic phases. The focus of this study was put on the qualification of different micromagnetic techniques and different measurement systems under conditions similar to the real ones during production, which is crucial for implementation of a property‐controlled flow forming process. The investigation was carried out on tubular specimens produced by flow forming, which have different content of α′‐martensite. To characterize the sensitivity of the sensors, different contact conditions between sensors and workpieces were reproduced. MBN sensors are suitable for detecting amount of α′‐martensite, but the measurements are affected by the surface roughness. This entails that the calibration models for MBN sensors must take account of these effects. EC sensors show a closer match with the amount of α′‐martensite without having major affectation by other effects.

Optimizing Communication for Latency Sensitive HPC Applications on up to 48 FPGAs Using ACCL - Meyer, Marius; Kenter, Tobias; Petrica, Lucian; O’Brien, Kenneth; Blott, Michaela; Plessl, Christian (Lecture Notes in Computer Science)
Most FPGA boards in the HPC domain are well-suited for parallel scaling because of the direct integration of versatile and high-throughput network ports. However, the utilization of their network capabilities is often challenging and error-prone because the whole network stack and communication patterns have to be implemented and managed on the FPGAs. Also, this approach conceptually involves a trade-off between the performance potential of improved communication and the impact of resource consumption for communication infrastructure, since the utilized resources on the FPGAs could otherwise be used for computations. In this work, we investigate this trade-off, firstly, by using synthetic benchmarks to evaluate the different configuration options of the communication framework ACCL and their impact on communication latency and throughput. Finally, we use our findings to implement a shallow water simulation whose scalability heavily depends on low-latency communication. With a suitable configuration of ACCL, good scaling behavior can be shown to all 48 FPGAs installed in the system. Overall, the results show that the availability of inter-FPGA communication frameworks as well as the configurability of framework and network stack are crucial to achieve the best application performance with low latency communication.

A Computation of the Ninth Dedekind Number Using FPGA Supercomputing - Van Hirtum, Lennart; De Causmaecker, Patrick; Goemaere, Jens; Kenter, Tobias; Riebler, Heinrich; Lass, Michael; Plessl, Christian (ACM Transactions on Reconfigurable Technology and Systems)
This manuscript makes the claim of having computed the 9th Dedekind number, D(9). This was done by accelerating the core operation of the process with an efficient FPGA design that outperforms an optimized 64-core CPU reference by 95x. The FPGA execution was parallelized on the Noctua 2 supercomputer at Paderborn University. The resulting value for D(9) is 286386577668298411128469151667598498812366. This value can be verified in two steps. We have made the data file containing the 490 M results available, each of which can be verified separately on CPU, and the whole file sums to our proposed value. The paper explains the mathematical approach in the first part, before putting the focus on a deep dive into the FPGA accelerator implementation followed by a performance analysis. The FPGA implementation was done in Register-Transfer Level using a dual-clock architecture and shows how we achieved an impressive FMax of 450 MHz on the targeted Stratix 10 GX 2,800 FPGAs. The total compute time used was 47,000 FPGA hours.

Optimisation and Evaluation of Breadth First Search with oneAPI/SYCL on Intel FPGAs: from Describing Algorithms to Describing Architectures - Olgu, Kaan; Kenter, Tobias; Nunez-Yanez, Jose; Mcintosh-Smith, Simon (Proceedings of the 12th International Workshop on OpenCL and SYCL)

Gewerblich-technische Lehrkräftebildung in Deutschland - Analyse der Einflüsse auf das akademische Selbstkonzept von Lehramtsstudierenden technischer (beruflicher) Fachrichtungen - Vernholz, Mats (Jahrbuch der berufs- und wirtschaftspädagogischen Forschung 2024)

Context-specific adaptation for head fakes in basketball: a study on player-specific fake-frequency schedules - Güldenpenning, Iris; Böer, Nils Tobias; Kunde, Wilfried; Giesen, Carina G.; Rothermund, Klaus; Weigelt, Matthias (Psychological Research)
In basketball, an attacking player often plays a pass to one side while looking to the other side. This head fake provokes a conflict in the observing opponent, as the processing of the head orientation interferes with the processing of the pass direction. Accordingly, responses to passes with head fakes are slower and result in more errors than responses to passes without head fakes (head-fake effect). The head-fake effect and structurally similar interference effects (e.g., Stroop effect) are modulated by the frequency of conflicting trials. Previous studies mostly applied a block-wise manipulation of proportion congruency. However, in basketball (and also in other team sports), where different individual opponents can be encountered, it might be important to take the individual frequency (e.g., 20% vs. 80%) of these opponents into account. Therefore, the present study investigates the possibility to quickly (i.e., on a trial-by-trial basis) reconfigure the response behavior to different proportions of incongruent trials, which are contingent on different basketball players. Results point out that participants indeed adapted to the fake-frequency of different basketball players, which could be the result of strategic adaptation processes. Multi-level analyses, however, indicate that a substantial portion of the player-specific adaptation to fake frequencies is accounted by episodic retrieval processes, suggesting that item-specific proportion congruency effects can be explained in terms of stimulus-response binding and retrieval: The head orientation (e.g., to the right) of a current stimulus retrieves the last episode with the same head orientation including the response that was part of this last episode. Thus, from a theoretical perspective, an attacking player would provoke the strongest detrimental effect on an opponent if s/he repeats the same head movement but changes the direction of the pass. Whether it is at all possible to strategically apply this recommendation in practice needs still to be answered.

Forecasting economic growth by combining local linear and standard approaches - Fritz, Marlon; Forstinger, Sarah; Feng, Yuanhua; Gries, Thomas (Journal of Applied Statistics)

Energy and sustainability: a balanced energy transition strategy - Kolosok, Svitlana; Myroshnychenko, Iuliia; Gries, Thomas (The Elgar Companion to Energy and Sustainability)